The challenges and coping strategies of communication partners of older adults with disabling hearing loss using assistive hearing technology. a South African study - Mustapha, Safoora (Department of Health and Rehabilitation Sciences, 2023)
The effects of disabling hearing loss can create communication barriers that do not only affect the person with hearing loss (PHL), but also the communication partner's (CP) quality of life. Literature has previously been centred around the individual with hearing loss, thus leaving an information gap in South Africa that focuses on providing family centred care that includes the CP in the audiological rehabilitation process. It is important for hearing health professionals to consider the CP's wellbeing when managing older adults with hearing loss, as they have been found to play a significant role in the audiological rehabilitation process. Therefore, exploring the Goal Sharing for Partners Strategy (GPS) tool in a South African context will contribute to the knowledge in the field of audiological rehabilitation. Furthermore, gaining insight into the challenges and coping strategies that CPs experience will improve on the approach to the service provided in audiological rehabilitation. A qualitative research design was employed with a sample of 10 couples who completed the GPS tool and semi-structured interviews. The data was analysed using thematic analysis. The results revealed four overarching themes that presented the effects of disabling hearing loss on the CP. The impact of disabling hearing loss resulted in daily life communication challenges for the CP. These challenges affected CPs emotionally as well as transformed the way they communicated in their relationships, however the values, beliefs and personality of the CPs allowed them to cope and develop resilience to the burden of third-party disability. Additionally, the usability questionnaire demonstrated that the GPS tool was an appropriate tool to use in South Africa when adopting a family centred approach to audiological rehabilitation and was most beneficial when implemented as an interview guide administered by an audiologist. The information from this study can be used to provide support to other CPs as well as enhance the success of audiological rehabilitation for PHLs through a family centred approach.